Resumption of postpartum ovarian activity in goats as affected by kidding season and body condition score under Egyptian conditions - ABSY, G; ABUZEAD, S M M; ZEIDAN, A E (The Indian Journal of Animal Sciences, 2014)
Female Baladi goats (45) were used to study the effects of kidding season and body condition score (BCS) on theresumption of postpartum ovarian activity. Out of 45 does, 12, 11, 10 and 12 were kidding during winter, spring summer and autumn respectively. Does within each season were allocated into 2 categories, those having low and medium BCS.Postpartum ovarian activity was monitored by measuring progesterone concentration in the sera samples that were collected twice weekly starting from day 14 up to week 8 postpartum. The results revealed that the percentages of does ovulated Within 8 weeks postpartum were 41.67, 54.55, 70 and 83.33% for animals that were kidding during winter, spring, summer and autumn respectively. Percentages of the resumption of ovarian activity of the does kidding during summer or autumn were sigmficantly (P